Replication Factor C3 of Schizosaccharomyces pombe, a Small Subunit of Replication Factor C Complex, Plays a Role in Both Replication and Damage Checkpoints - Shimada, Midori (The American Society for Cell Biology, 1999)
We report here the isolation and functional analysis of the rfc3(+) gene of Schizosaccharomyces pombe, which encodes the third subunit of replication factor C (RFC3). Because the rfc3(+) gene was essential for growth, we isolated temperature-sensitive mutants. One of the mutants, rfc3-1, showed aberrant mitosis with fragmented or unevenly separated chromosomes at the restrictive temperature. In this mutant protein, arginine 216 was replaced by tryptophan. Pulsed-field gel electrophoresis suggested that rfc3-1 cells had defects in DNA replication. rfc3-1 cells were sensitive to hydroxyurea, methanesulfonate (MMS), and gamma and UV irradiation even at the permissive temperature, and the viabilities after these treatments were decreased. Using cells synchronized in early G2 by centrifugal elutriation, we found that the replication checkpoint triggered by hydroxyurea and the DNA damage checkpoint caused by MMS and gamma irradiation were impaired in rfc3-1 cells. Association of Rfc3 and Rad17 in vivo and a significant reduction of the phosphorylated form of Chk1 in rfc3-1 cells after treatments with MMS and gamma or UV irradiation suggested that the checkpoint signal emitted by Rfc3 is linked to the downstream checkpoint machinery via Rad17 and Chk1. From these results, we conclude that rfc3(+) is required not only for DNA replication but also for replication and damage checkpoint controls, probably functioning as a checkpoint sensor.